Towards the development of a screening tool for Anorexia Nervosa in men - Reeves, Megan Moya (University of the Witwatersrand, Johannesburg, 2022)
Anorexia Nervosa (AN) in men is still not wholly understood and is often misdiagnosed. The primary aim of this tri-phasal exploratory, mixed methods study was to propose content domains and items that may be used to inform the development of future quantitative tests to screen for AN in men. It has been reported that there is currently no quantitative instrument available, which has been specifically designed to measure anorexic symptomatology in men (Darcy et al., 2012; Murray et al., 2012). The quantitative content domains and test items developed in this study may be used in future self-report screening measures to help improve the accurate recognition of AN symptoms in men. These items will help to counter the effects of gender biases evident in current AN screening tools and biases held by clinicians and psychiatrists that are reported when screening for AN in men. These test items and content domains were developed in the third phase of this study and were derived from the findings of the first two phases. In phase one, a comprehensive thematic list of symptoms reportedly experienced by men diagnosed with AN was developed from an integrative literature review of peer-reviewed journal articles published between July 2000 to July 2013 on PsychINFO, SA ePublications, and Google Scholar. The data from phase one were supplemented by a thematic analysis of 14 interviews with South African clinical psychologists and psychiatrists, conducted under phase two, which deconstructed their beliefs regarding AN in men. Ultimately, the study’s three phases cumulatively showed how the symptoms reportedly experienced by men differed to those of women, deconstructed the beliefs held by a sample of South African clinical psychologists and psychiatrists, recommended a gender sensitive and identity based conceptualisation of AN that served to explicate theory, and finally proposed original test items that may be used in future research to develop a test to more validly and reliably screen for AN symptomatology in men.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Psychology, to the Faculty of Humanities, School of Human and Community Development, at the University of the Witwatersrand, 2022
Keywords: Anorexia Nervosa; Masculinity; Identity; Gender bias; Diagnosis; Screening items; Stigma; Body image and symptomatology; UCTD; SDG-3: Good health and well-being